Возможности вейвлетного анализа к задаче оценки вариабельности ритма сердца - Величко, О. Н.; Попов, A. B. (ХНУРЭ, 2008)
Advantages of wavelet technologies to the cardiac rhythmograms analysis are justified. Advanced claims to the sequence of cardiac rhythmograms, including interpolation step and rhythmmogram length. Impact of tip effects to the wavelet spectrum was considered. Wavelet analysis capabilities for research slow waves of different orders are revealed.
Keywords: ритм сердца; биомединженерия